(untitled) (The Agriculturists, 2016)
The study was conducted to evaluate the extent of variability among the small grain aromatic (SGA) rice (Oryza sativa L.) genotypes for yield and yield components. Twenty four popular SGA rice genotypes were evaluated for yield and yield contributing characters in BRAC Agricultural Research and Development Centre, Gazipur, Bangladesh. BRRI dhan34 was used as check variety. Highest grain yield per plant was observed in Chinikanai-1, which was followed by Kalijira PL-9, Kalijira PL-3 and Badshabhog. Chinikanai-1 had the highest number of grains per panicle. Correlation analysis revealed that the number of panicles per plant (r = 0.646) and number of grains per panicle (r = 0.525) had the positive contribution to grain yield. Based on sensory test, it was found that 18 genotypes were scented and six were lightly scented. After evaluation of yield components, four genotypes namely Chinikanai-1, Kalijira PL-9, Kalijira PL-3 and Badshabhog were selected as outstanding genotypes, which can be used as potential breeding materials for sub-tropical environment of Bangladesh. The Agriculturists 2015; 13(2) 17-24